Efektivitas Pelayanan Terpadu Satu Pintu dalam Perspektif Kinerja Pelayanan Publik: Studi di Kabupaten Maluku Tengah - Liklikwatil, Debyella Cesya; Sahetapy, Petronela; Normawati, Normawati (MAN 4 Kota Pekanbaru, 2026)
This study examines the effectiveness of One-Stop Integrated Services (PTSP) in a local government context, focusing on service performance dimensions and human resource competencies. A quantitative descriptive survey was conducted among 23 civil servants at the Investment and One-Stop Service Office in Maluku Tengah Regency. The findings indicate that PTSP implementation demonstrates a high level of effectiveness in terms of target accuracy, resource adequacy, process speed, and organizational integration. Employee competencies in communication, time management, problem-solving, and adaptability were found to support service effectiveness. The results highlight the importance of aligning institutional design with human capacity in achieving integrated public service performance. This study contributes empirical evidence from Eastern Indonesia and offers implications for strengthening organizational coordination and capacity-building strategies in local public service institutions.